Evalution of women economic development program (WEDA) in developing women entrepreneurship in Sariket Division, Sarawak. - Man, Norsida (2010)

(untitled)
Women entrepreneurs in Malaysia have increased significantly since independence and a handful of them have even succeeded in establishing and managing huge businesses in the country. In line with the government indigenous women entrepreneurship empowerment objectives, the Women Economic Development (WEDA) programme under the Department of Agriculture, Sarikei Division of Sarawak was established to strengthen the entrepreneurial potential of local women. In this study, 30 female participants from the WEDA programme were involved. The CIPP (Context, Input, Process and Product) Model Evaluation was used to assess the programme's effectiveness towards women participants in entrepreneurship, especially those involved in agriculture-based activities. The majority of the respondents was Ibans with the age group ranged from 36 to 45 years. The target component one (Women Entrepreneurs Development) managed to achieve only 35% of the target as measured by the changes in total sales and net profit after participating in the WEDA programme, while target component two (Family Income Diversification) managed to achieve 15% of the set target. The results, however, suggest that participants' drive for success is not raised to a greater extent and there is a lack of effort due to the high cost of operation, weather conditions and marketing problems. However, the participants felt the positive changes especially in business knowledge, skill acquisition and entrepreneurial operations.